Pengaruh Model Pembelajaran Reciprocal Teaching Terhadap Keterampilan Menulis Puisi Di Kelas X SMA Swasta Dharma Pancasila Medan - Vita Rosari Sinurat; Atika Wasilah (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The learning model is one of the main components in learning activities. Learning objectives can be realized if an efficient learning model is used so that it can help and facilitate learning activities. The 2013 curriculum makes teachers act as facilitators, allowing students to develop their information through cognitive stages. One of the teacher's responsibilities is to direct students' learning activities in achieving learning outcomes. Thus, educators must have the ability to explain lessons (Joharis & Jaya, 2019). Joharis & Naelofaria (2021) say that the learning process is no longer enough to just listen to the teacher's explanation of the topic, but students also carry out activities. By applying the reciprocal learning model, a teacher can optimize learning activities in the classroom to improve students' writing skills. Sriyani, et al (2018) stated that reciprocal teaching is an independent learning activity that is realized by students in obtaining good learning grades through the independent learning process and students are successful in explaining their findings to other individuals.